PERAN SPIRITUAL CAPITAL DALAM MENINGKATKAN KETAHANAN USAHA PENDIDIKAN ISLAM DI ERA DISRUPSI: KAJIAN LITERATURE REVIEW - Muhammad Sodiqul Fikri; Rezki Oktoberi; Bambang Sri Anggoro; Sovia Mas Ayu (EDUCATIONAL : Jurnal Inovasi Pendidikan & Pengajaran, 2026)
ABSTRACT The acceleration of digitalization, the rapid advancement of artificial intelligence, and ongoing social transformation in the era of disruption have compelled Islamic educational institutions to strengthen their adaptive capacity while preserving the Islamic values that constitute their institutional identity. Although previous studies have examined spiritual leadership, digital transformation, and organizational resilience, a comprehensive synthesis explaining the relationship between spiritual capital and the resilience of Islamic educational institutions remains limited. This study presents a conceptual synthesis of the role of spiritual capital in strengthening the resilience of Islamic educational institutions. A Systematic Literature Review following the PRISMA 2020 guidelines was employed. Literature searches were conducted in Google Scholar, Scopus, Semantic Scholar, Garuda, and DOAJ, yielding 75 articles, of which 30 publications from 2022–2026 met the inclusion criteria and were subsequently analyzed using content analysis. The synthesis demonstrates that spiritual capital functions as a strategic resource that integrates leadership, human resource development, organizational culture, digital transformation, learning innovation, and organizational resilience within the management of Islamic educational institutions. These findings extend the understanding of spiritual capital as integrative capital, aligning Islamic values with contemporary educational management practices. The resulting conceptual framework provides both an academic foundation and a practical reference for developing institutional strategies that are adaptive, sustainable, and firmly grounded in Islamic identity amid the challenges of the disruptive era. ABSTRAK Percepatan digitalisasi, perkembangan kecerdasan buatan, dan perubahan sosial pada era disrupsi mendorong lembaga pendidikan Islam untuk memperkuat kapasitas adaptasi tanpa melepaskan nilai-nilai keislaman yang menjadi identitas kelembagaan. Meskipun berbagai penelitian telah membahas kepemimpinan spiritual, transformasi digital, maupun organizational resilience, sintesis yang menjelaskan keterkaitan spiritual capital dengan ketahanan lembaga pendidikan Islam masih relatif terbatas. Artikel ini menyajikan sintesis konseptual mengenai peran spiritual capital dalam memperkuat ketahanan lembaga pendidikan Islam. Kajian dilakukan menggunakan pendekatan Systematic Literature Review dengan pedoman PRISMA 2020. Penelusuran literatur pada Google Scholar, Scopus, Semantic Scholar, Garuda, dan DOAJ mengidentifikasi 75 artikel, kemudian diseleksi menjadi 30 artikel terbitan 2022–2026 yang memenuhi kriteria inklusi untuk dianalisis melalui teknik content analysis. Sintesis menunjukkan bahwa spiritual capital berfungsi sebagai modal strategis yang menghubungkan kepemimpinan, pengembangan sumber daya manusia, budaya organisasi, transformasi digital, inovasi pembelajaran, dan organizational resilience dalam pengelolaan lembaga pendidikan Islam. Temuan ini memperluas pemahaman mengenai spiritual capital sebagai integrative capital yang menyelaraskan nilai-nilai keislaman dengan praktik manajemen pendidikan modern. Kerangka konseptual yang dihasilkan memberikan landasan akademik sekaligus rujukan bagi pengembangan strategi kelembagaan yang adaptif, berkelanjutan, dan tetap berorientasi pada penguatan identitas keislaman di tengah dinamika era disrupsi.